1. The problem statement, all variables and given/known data x^2y' + 2xy = 5y^3 2. Relevant equations Bernoulli Equation 3. The attempt at a solution so... v=y^-2, y=v^(-1/2) y' = -1/2v'v^(-3/2) moving everything over... y'/y^3 + 2/(xy^2) = 5/x^2 and plugging everything in... -1/2v' + 2v/x = 5/x^2 v' - 4v/x = -10/x^2 v' - 4v/x = 0 dv/dx = 4v/x dv/v = 4dx/x ln v = 4 ln x + C v = C(x)x^4 v' = C'(x)x^4 + C(x)4x^3 C'(x)x^4 + C(x)4x^3 - 4C(x)x^4/x = 5/x^2 C'(x)x^4 = 5/x^2 C'(x) = 5/x^6 C(x) = -x^-5 + C v = (-x^-5 + C)x^4 y = 1/(v)^(1/2) y^2 = 1/((-x^-5 + C)x^4) ... which is wrong. Could someone point me in the right direction?